Retention force and fatigue strength of overdenture attachment systems - Botega, D. M.; Mesquita, M. F.; Henriques, GEP; Vaz, Luis Geraldo [UNESP] (Blackwell Publishing, 2004)
This study evaluated retention force and fatigue resistance of two overdenture attachment systems. Twenty samples (O-ring and Bar-Clip) from two manufacturers (Conexao Sistemas de Protese and Lifecore Biomedical) were prepared and divided into four groups: (i) Conexao/O-ring; (ii) Conexao/Bar-Clip; (iii) Lifecore/O-ring and (iv) Lifecore/Bar-Clip, with five samples in each group. They were submitted to mechanical fatigue test using a servohydraulic machine performing 5500 cycles of insertion and removal (f=0.8 Hz), immersed in artificial saliva. Retention force values were obtained three times (0, 3000 and after 5500 cycles) simulating the clinical service, using a tensile strength at 1 mm min(-1) and load cell of 1 kN. Data were analysed with analysis of variance and Tukey's test at 5% level. Results showed that Conexao/Bar-Clip specimens had significantly higher retention values than Lifecore/Bar-Clip (44.61 and 18.44 N, respectively), Conexao/O-ring specimens had significantly lower values than Lifecore/O-ring (13.91 and 19.75 N, respectively). Conexao/Bar-Clip values were always significantly higher than those of Conexao/O-ring group (44.61 and 13.91 N, respectively). Lifecore (O-ring and Bar-Clip) presented similar values (19.75 and 18.44 N, respectively). The systems evaluated showed satisfactory retention force values, before and after fatigue testing. Conexao/Bar-Clip specimens presented the highest values. A 5-year simulation of insertion and removal did not decrease retention values or fracture components.
Keywords: overdentures; attachments; osseointegrated implants; mechanical properties; fatigue strength; retention